2018
DOI: 10.1021/acs.jced.8b00326
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cosolvents DMSO and Glycerol on the Self-Assembly Behavior of SDBS and CPC: An Experimental and Theoretical Approach

Abstract: The study of the effect of cosolvents on the micellization of ionic surfactants is relevant in different industrial applications. In this article, we studied the effects of binary aqueous mixtures of DMSO and glycerol on the micellization and thermodynamic behavior of sodium dodecyl benzenesulfonate (SDBS) and cetylpyridinium chloride (CPC) in the range of (293.15–308.15) K. The electrical conductivity method was employed to determine the parameters of micellization such as the critical micellar concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 80 publications
(119 reference statements)
1
13
0
Order By: Relevance
“…The intermolecular free length, in table 3, indicates that the molecules are much more closely packed, thus implying the existence of the strong solute solvent interaction inside the mixture, evident from the figure 5. The presence of the strong binding forces inside the liquid system between solute and solvent is confirmed by the increasing values of Vander Waal's constants with the temperature, in table 3 [29][30][31][32].…”
Section: (V) Intermolecular Free Length ( ): -mentioning
confidence: 99%
“…The intermolecular free length, in table 3, indicates that the molecules are much more closely packed, thus implying the existence of the strong solute solvent interaction inside the mixture, evident from the figure 5. The presence of the strong binding forces inside the liquid system between solute and solvent is confirmed by the increasing values of Vander Waal's constants with the temperature, in table 3 [29][30][31][32].…”
Section: (V) Intermolecular Free Length ( ): -mentioning
confidence: 99%
“…The noncovalent interaction index (NCI) , was used to qualitatively identify the areas where weak interactions predominate, the origin of which may be dispersive in nature, hydrogen bonds, dipole–dipole interactions, or repulsive steric effects, which are based on the sign of the second eigenvalue (λ 2 ) of the electron density matrix (Hessian matrix) as is described in the literature. , We also calculate the intensity of the noncovalent interactions by using the independent gradient (IGM) approach. , In the framework of the IGM approach, the descriptor δ g inter identifies the gradient attenuation of the electronic density (ED) due to interactions resulting from the electron sharing between fragments. Plotting δ g inter isosurfaces provides a chemically intuitive picture of the noncovalent forces between such fragments.…”
Section: Computational Detailsmentioning
confidence: 99%
“…A similar trend in ΔS m 0 values has been observed for other cationic surfactants in mixed media with an increase in temperature. 17,45,64,65 Unlike CPCl, a decrease in the values of ΔS m 0 was not observed with a rise in temperature for CPBr except at 7.5% PrOH−WR mixed media (Figure S4b; Supporting Information).…”
Section: Introductionmentioning
confidence: 96%
“…16 Sharma et al have shown that the micellization of cetylpyridinium chloride (CPCl) and sodium dodecyl benzenesulfonate (SDBS) is suppressed by the rise in temperature as well as the inclusion of cosolvents (dimethyl sulfoxide/glycerol) in the aqueous medium. 17 Furthermore, mixed media (ethylene glycol−water) has been reported as a promising media to remove the toxic flume SO 2 gas. 18 Considering the significance of surfactant aggregation in various polar organic solvents−water mixed media and useful outcome of the studies, it is significant to have knowledge on the surfactant's micellization in mixed media which can offer different polarities based on the compositions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation